2022
DOI: 10.1161/jaha.121.024865
|View full text |Cite
|
Sign up to set email alerts
|

Association of Night‐to‐Night Adherence of Continuous Positive Airway Pressure With Day‐to‐Day Morning Home Blood Pressure and Its Seasonal Variation in Obstructive Sleep Apnea

Abstract: Background The aim of this study was to investigate the association between night‐to‐night adherence to continuous positive airway pressure (CPAP) therapy and both home blood pressure (BP) level on the following day and seasonal variation in home BP in patients with obstructive sleep apnea. Methods and Results We analyzed 105 participants who had been diagnosed with obstructive sleep apnea (average apnea‐hypopnea index, 49.7±18.4 per hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Results of an experimental study using Canine model clearly revealed that obstructive sleep apnea increased daytime but not nighttime BP [24] probably because of increased central nervous system activity. Furthermore, findings from previous studies, namely sleep apnea was independent factor for relatively higher morning BP compared with evening BP [25] and continuous positive airway pressure therapy for patients with sleep apnea reduced morning BP [26], supporting our results. Nocturnal urination frequency strongly and positively associated with sleep BP independent of sleep efficiency [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…Results of an experimental study using Canine model clearly revealed that obstructive sleep apnea increased daytime but not nighttime BP [24] probably because of increased central nervous system activity. Furthermore, findings from previous studies, namely sleep apnea was independent factor for relatively higher morning BP compared with evening BP [25] and continuous positive airway pressure therapy for patients with sleep apnea reduced morning BP [26], supporting our results. Nocturnal urination frequency strongly and positively associated with sleep BP independent of sleep efficiency [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, only 55.5% of the patients developed a systolic decrease of at least 5 mmHg Finally, it may be scrutinized whether the quality of treatment or the patients’ adherence was too low to produce are more robust association. Indeed, adherence to CPAP therapy is negatively associated with morning BP [ 13 ]. The decrease of daytime sleepiness from baseline to follow-up and the mean CPAP use of 4.8 h per night; however, contradict these assumptions in the present population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, telemedicine support could help improve the adherence to CPAP use in patients with sleep apnea. Good CPAP adherence has been negatively associated with morning home BP on the following day [44], which would result in the reduction in CVD events related to day-by-day home BP variability [45][46][47].…”
Section: Telemedicine In Other Cardiovascular Risk Factorsmentioning
confidence: 99%